Introduction to Thermoelectricity - Goldsmid, H. Julian (Springer Series in Materials Science,, 2010)
Introduction to Thermoelectricity is the latest work by Professor Julian Goldsmid drawing on his 55 years experience in the field. The theory of the thermoelectric and related phenomena is presented in sufficient detail to enable researchers to understand their observations and develop improved thermoelectric materials. The methods for the selection of materials and their improvement are discussed. Thermoelectric materials for use in refrigeration and electrical generation are reviewed. Experimental techniques for the measurement of properties and for the production of thermoelements are described. Special emphasis is placed on nanotechnology which promises to yield great improvements in the efficiency of thermoelectric devices. Chapters are also devoted to transverse thermoelectric effects and thermionic energy conversion, both techniques offering the promise of important applications in the future.